KONJUNGSI DALAM NOVEL PRIDE AND PREJUDICE KARYA JANE AUSTEN - PESIK, VICKY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
A B S T R A C T Conjunction is a word used to connect words, phrases and clauses. Conjunction shows the relationship between sentence elements that they connect. This study is an attempt to describe and analyze the conjunction in the novel â€œPride and Prejudiceâ€ written by Jane Austen. The writer analyzed and classified these conjunctions according to their types and functions which the data have been taken from the novel. This investigation has been done through bibliography research and it used the concept of Aarts and Aarts. The results showed that there are three kinds of conjunction in the novel â€œPride and Prejudiceâ€, they are coordinating conjunctions, subordinating conjunctions and correlative conjunctions. The coordinating conjunction can link two words â€˜they are silly and ignorant like other girlsâ€™, two phrases â€˜her ease and good spirits increasedâ€™ and two clauses â€˜jumping after stiles and springing over puddlesâ€™. The subordinating conjunction can link a clause with another clause or other constituents in a sentence â€˜I had hope that our sentiments coincidedâ€™, and the correlative conjunction are coordinating words that work in pairs to join words â€˜neither Jane nor Elizabethâ€™, phrases â€˜can tell us whether it is like or notâ€™ and clauses â€˜she was perfect either making some inquiry, or looking at his pageâ€™, or whole sentence. It is expected that this study can be continued by students of English Department and those who are interest in learning one of the aspects of English, in this case conjunction. Key words: Conjunction, Pride and Prejudice